'Kids save lives': why schoolchildren should train in cardiopulmonary resuscitation. Issue 3 (June 2015) - Bohn, Andreas; Lukas, Roman P.; Breckwoldt, Jan; Böttiger, Bernd W.; Van Aken, Hugo
Abstract : Purpose of review: Quick initiation of basic life support (BLS) by laypersons is one of the most successful strategies in the fight against sudden cardiac death. In developed countries, cardiac arrest is still a major contributor to avoidable death, and despite the fact that more than 50% of all cardiac arrests are witnessed, layperson BLS is performed in less than 20%. To improve this situation, BLS training in schools has been established. Recent findings: Cardiopulmonary resuscitation (CPR) instruction including the use of automatic external defibrillators (AEDs) has shown to be feasible even for young schoolchildren, and there is an indication that respective programmes are effective to enhance patient outcome on a population basis. Earlier training may even lead to more sustainable results; however, it is reasonable to implement adjusted curricula for different child ages. The programme 'Kids Save Lives' recently endorsed by the WHO will help promoting school-based BLS training worldwide demanding education on CPR for all pupils starting at least at age 12. Summary: Resuscitation training in schools can help to increase the amount of BLS-trained population. Social skills of pupils can be improved and training can be successfully implemented independently of the pupils' age and physique.